Red deer habitat selection and movements in relation to roads1. Issue 1 (8th October 2012) - Meisingset, Erling L.; Loe, Leif E.; Brekkum, Øystein; Van Moorter, Bram; Mysterud, Atle
Abstract: Roads affect wildlife in many direct and indirect ways. For ungulates, roads may inhibit seasonal migration and may cause an effective loss of habitat due to avoidance. On the other hand, roadsides and associated agricultural lands offer high quality forage that may attract ungulates and increase the frequency of car accidents. Mitigating actions require detailed knowledge on space use in relation to roads. Using data from 67 global positioning system (GPS)‐marked red deer in Norway, we quantified 1) scale of avoidance of roads, 2) crossing frequency, and 3) selection of crossing sites. Red deer avoided roads only on a very local scale and only during daytime, with minor influence of variation in road size (traffic burden). Marked red deer crossed roads, on average, 2 times per day. Females crossed more frequently than males and crossings were most frequent during autumn and winter and during night. Deer selected forested crossing sites close to agricultural pastures, reflecting that roads are crossed most often on nightly feeding excursions. Our findings imply that red deer in our study area have adjusted to exploit feeding habitat close to roads at times of low traffic burden. The high frequency of crossings suggests a limited influence on seasonal migration patterns. The frequency at which red deer cross highways suggests that mitigation measures to reduce road mortality may be effective if targeted in the right areas. © 2012 The Wildlife Society.